Integrated water storage assessment in the Tana-Beles Sub-basin, Ethiopia - Taye, Meron Teferi; Assefa, T. T.; Ebrahim, Girma Yimer; Lautze, Jonathan F.; Seid, Abdulkarim (Springer, 2025)
In river basins with strong seasonal river fluctuation, water storage of various types is required to meet water demands. Water is stored in man-made reservoirs, groundwater aquifers, the soil, natural lakes and wetlands. Ideally, to meet any water demand, these water storage options could be used in an integrated manner. However, integrating suites of water storage options in the management for water, food, energy, and the environment is limited in practice. One of the reasons for this is the lack of knowledge on the volume and temporal dynamics of the different storage types. This study therefore assessed water storage in different storage types and their temporal dynamics using remote sensing and secondary data in the Tana-Beles sub-basin of Ethiopia. The results show that the active total storage volume in the sub-basin varies from 7.3 BCM to 16.2 BCM in dry and wet months, respectively. Lake Tana storage is the largest with 50% of total storage while built reservoirs only account for 2% of the same. Given different competing needs and constraints from each storage options not all the water in the storages can be utilized. Optimizing natural and built storage options in an integrated system can maximize water security gains.